SMART POULTRY WAKE-UP SYSTEM BERBASIS MIKROKONTROLER UNTUK MENUNJANG NAFSU MAKAN DAN KESEHATAN AYAM - Isminarti, Isminarti; Iriawan Eka Putra, Nur Azhary; Hamzah, Fauziah; Mustika, Alyah; Aiman, Ammar (JURNAL RAMATEKNO, 2025)
Modern poultry farming faces challenges in maintaining the activity and health of chickens, particularly at night when physical movement decreases and appetite declines. To address this issue, this study aims to design and test a microcontroller-based Smart Poultry Wake-Up System as an automatic alarm system to stimulate chickens to become more active. This research uses a quantitative method with an experimental approach, utilizing Arduino Nano, RTC DS3231 module, relay, and a 24V buzzer. The system is programmed to activate the buzzer at specific times (00:00, 02:00, 04:00, and 06:00) to periodically wake the chickens. The test results show that the system successfully activated the buzzer according to the programmed schedule, both simultaneously and sequentially, without time delays. All hardware and software components functioned properly and stably. The conclusion of this study indicates that the automatic alarm system is a reliable and practical solution to support chicken activity. For future development, the system can be enhanced by adding environmental sensors and integrating IoT to improve monitoring efficiency and flexibility.